"I Swear to God, I Only Want People Here Who Are Losers!" Cultural Dissonance and the (Problematic) Allure of Azeroth. (20th June 2014) - Snodgrass, Jeffrey G.; Dengah, H. J. François; Lacy, Michael G.
<x xml:space="preserve">Abstract</x> We use ethnographically informed survey and interview data to explore therapeutic and problematic play in the online World of Warcraft (WoW). We focus on how game‐play in WoW is driven by shared and socially transmitted models of success that we conceptualize as cultural ideals. Our research reveals associations between having higher online compared to offline success, on the one hand, and gamers' reports about how their play both adds to and subtracts from their mental wellness, on the other. Fusing William Dressler's notion of "cultural consonance" (an individual's relative consistency with his or her culture) with Leon Festinger's "cognitive dissonance" (the tendency of individuals to suffer distress when they cannot eliminate incompatibilities in conflicting beliefs and attitudes), we develop the notion of "cultural dissonance, " which in this context refers to how conflicts between online and offline lives, and also subsequent attempts to minimize the conflicts through psychological negotiations, impact gamers' mental health.